Quality Control Analysis Using the PDCA (Plan, Do, Check, Action) Method to Reduce Carton Packaging Returns at PT. App Purinusa Ekapersada Demak - Intany Salsabiela; Riandhita Eri Werdani (Journal of Vocational Studies on Applied Research, 2026)
PT APP Purinusa Ekapersada Demak is a packaging company that produces carton sheets and carton boxes for various industries, with more than 100 customers in 2024. However, the company is facing an increase in the number of products returns due to damage that occurs during the distribution process, product non-conformity to the specified specifications, and product handling procedures that are still not running optimally. Analysis of production data and the 2022-2024 return period shows that the total return of carton sheets and carton boxes exceeds the maximum limit set, with the main damage being rust. This study aims to control quality by implementing the PDCA (Plan, Do, Check, Action) method to reduce the return rate and increase production efficiency. The research method uses a qualitative descriptive approach with observation, interview, and documentation techniques. The analysis was carried out through a Pareto diagram to determine problem priorities, a cause-and-effect diagram (fishbone) to identify the main causes, and 5W + 1H and control charts for process evaluation and monitoring. The implementation results showed a significant decrease in the level of damage, especially for rust defects, after improvements were made to human, material, machine, method, and environmental factors. Key recommendations include operator training, evaluation of supplier governance assessments, routine machine maintenance, and updating of standard operating procedures (SOPs) to ensure continuous improvement and increase customer satisfaction.